1-(2-Fluorobenzylideneamino)pyridinium bis(1,2-dicyanoethene-1,2-dithiolato)nickelate(II) - Zhang, Hui (International Union of Crystallography, 2009)
In the title complex, (C(12)H(10)FN(2))(2)[Ni(C(4)N(2)S(2))(2)], the anion lies on an inversion center with the Ni(II) ion coordinated by four S atoms in a slightly distorted square-planar environment. In the unique cation, the dihedral angle between the benzene and pyridine rings is 7.1 (2) Å.